Verses of Faith and Devotion. Seeing, Reading, and Touching Monumental Crucifixes with Inscriptions (12th–13th century) - Marušić, Matko Matija (Studia Ceranea, 2016)
The paper discusses a group of monumental crucifixes from the 13th-century East Adriatic and Italy, pained or executed in low relief, that display a verse inscriptions on the transverse limb of the cross. The main scope of the paper is to examine the provenance of the text inscribed in order to yield clearer insight into their function, use and original location in the church interiors. The paper specifically aims at analyzing three monumental crucifixes from the East-Adriatic city of Zadar which, although have already been the subject of a respectable number of studies, have not attracted attention as objects of devotion. My interest, therefore, is turned towards verse inscription as their distinctive feature and, as I shall argue, a key aspect in understanding their function. Examining the nature of the text displayed, iconography and materiality of these crucifixes, my main argument is to demonstrate how these objects provoked a multi-faced response from their audience, since were experienced by seeing, hearing and touching respectively.